Night-to-Day Ratio Specified by 24-hour Blood Pressure Monitoring, Arterial Stiffness and Cardio-Ankle Vascular Index as Predictive Factors of Cardiovascular Risk - Havelkova, A; Dvorak, P; Pohanka, M; Dobsak, P; Siegelova, J; Cornelissen, G (Physiological research, 2025)
This study compares the interrelationships among different methods of determining predictive factors of cardiovascular risk: the Night-to-Day ratio (ND-R), Ambulatory Arterial Stiffness Index (AASI), Cardio-Ankle Vascular Index (CAVI), and Ankle-Brachial Index (ABI). A total of 8120 blood pressure measurements were obtained from 280 24h-ABPM records (29 values per daily record) of 20 patients who each provided two 7-day/24-hour monitoring sessions. For each of the two 7-day-24h-ABPM records, the ND-R and AASI were determined. CAVI and ABI were always examined at the beginning of each 7-day-24h-ABPM session. All 20 patients (12 men; 8 women; mean age 57+/-2.1 yrs; mean BMI 29.3+/-1.69 kg/m2; mean left ventricle ejection fraction 53+/-3.8 %) had chronic ischemic coronary artery disease. The correlation coefficients did not exceed 0.318. ND-R of SBP showed the highest methodological sensitivity, identifying 65 % of patients at increased risk, compared to 57.5 % for ND-R of DBP, 23.7 % for CAVI, and 2.5 % for AASI (up to 27.5 % by evaluating individual days). The different cardiovascular risk assessment methods (ND-R, AASI, CAVI and ABI) cannot be substituted for one another. No risk was demonstrated using ABI. Repeating the 7-day-24h-ABPM approximately 1 year apart (unless there is a change in medication or in clinical symptoms) revealed a significantly different results of the ND-R and AASI, which can be expected in approximately 25 % of patients. Key words Ambulatory blood pressure monitoring " Night-to-Day blood pressure ratio " Ambulatory Arterial Stiffness Index " Cardio-Ankle Vascular Index " Ankle Brachial Index " Ischemic heart disease.
Keywords: prediktivní hodnota testů; Cardio Ankle Vascular Index; Risk Factors; ženské pohlaví; lidé; ambulantní monitorování krevního tlaku; senioři; Vascular Stiffness; Predictive Value of Tests; Aged; lidé středního věku; Cardiovascular Diseases; Circadian Rhythm; Time Factors; Humans; cévní index srdce-kotník; rizikové faktory kardiovaskulárních chorob; Ankle Brachial Index; cirkadiánní rytmus; Heart Disease Risk Factors; kardiovaskulární nemoci; mužské pohlaví; Male; Blood Pressure Monitoring, Ambulatory; rizikové faktory; časové faktory; Blood Pressure; tuhost cévní stěny; krevní tlak; Middle Aged; Female; tlakový index kotník-paže